Studi Eksperimental Pengaruh Medan Magnet Terhadap Kinerja Mesin Otto 108 cc Menggunakan Variasi Jarak Antar Medan Magnet - Sanjaya Baroar Sakti Nasution; Mulfi Hazwi (Retii, 2016)
This research conducted by experimental analyze the performance of Otto four stroke engine, single cylinder with 108 cc, and work with ratio compression ,2:1. Fuel that used is pertalite RON 90. The research use single and double magnet with 2500 Gauss that variate 5 cm, 10 cm , and 15 cm of distance. The result from experimental test that use magnet has reduce spesific fuel consumtion until 29,8 %, improve the engine torsion up to 17, 4%, engine power 16,7 %. Increase thermal efficiency up to 7,51 %. Reduce CO and HC level up to 27% and 18,9 %. Increase CO2 level up to 19,67%  and reduce O2 level up to 21,72 %. Keyword:  Otto engine 108 cc, Magnet 2500 Gauss, Engine performance, Gas emission.